An exploratory application of full-grown Cetoscarus Bicolor Scales into a translucent for non-structural interior surface finishing materials - Sim, Maria Celiza Z. (College of Home Economics, University of the Philippines Diliman, 2018)
Abstract: This explorative applied study was conducted to discover the potential of throwaway full grown cetoscarus bicolor scales. The study specifically aimed to develop an exploratory application of full-grown cetoscarus bicolor scales into a translucent panel for non-structural interior surface finishing material; to determine the characteristics and material components of full-grown cetoscarus bicolor scales that makes it unique and useful; to create a translucent panel that is functionally and aesthetically appealing using full-grown cetoscarus bicolor scales; and to design a non- structural interior surface finishing material prototype using the new developed fish scale translucent panel in interior design. The data gathering and hands on actual procedures were lifted, revised, and based from public books and limited existing researches related to fish scales. Data were gathered through an explorative testing of sequential method of experimentations. Documentation was conducted through photographs, videos, in-depth interviews, pretest and post test, material testing, conceptualizing with technical drawings, and actual application in interior design as movable furniture prototypes. Results showed that the new developed fish scale translucent material is applicable in interior design as non-structural interior surface finishing material. The results of the study may introduce translucent interior surface finishing material innovation as alternative option, and may propose additional livelihood for Filipino community especially for fish vendors and fishermen. Further in-depth studies with advanced applications in maximizing the diversity of fish scales are recommended.